Individualized educational planning ICF based. Testing and monitoring of the IEP-ICF UniSalento model - Pinnelli, Stefania; Fiorucci, Andrea (Form@re - Open Journal per la formazione in rete, 2021)
In light of the regulatory provisions provided by the Implementing Decrees of the Law 107/2015, starting from the cultural revolution that the ICF proposes, educational institutions are called upon to reconsider the individualized planning provided for the safeguard of pupils with disabilities. In order to guide the teachers in the dialogue with the biopsychosocial perspective, the working group of the Center on New Technologies for Disability and Inclusion (CNTHI) of the University of Salento has launched a research and training path on the ICF-based Individualized Educational Planning. The outcome of the research is the formalization and subsequent testing of a IEP -ICF model. The paper describes the development phases of the model and presents the results of the experimentation and monitoring process implemented in some school institutions in the reference area. Progettazione educativa individualizzata su base ICF. Sperimentazione e monitoraggio del modello PEI-ICF UniSalento Alla luce delle disposizioni normative previste dai Decreti attuativi della L. 107/2015, le istituzioni scolastiche sono chiamate a ripensare la progettazione individualizzata a tutela dell’alunno con disabilità a partire dalla rivoluzione culturale che l’ICF propone. Allo scopo di guidare i docenti nell’interlocuzione con la prospettiva bio-psico-sociale, il gruppo di lavoro del Centro sulle Nuove Tecnologie per la disabilità e l’Inclusione (CNTHI) dell’Università del Salento ha avviato un percorso di ricerca e di formazione sulla progettazione educativa individualizzata in chiave ICF, il cui esito è rappresentato dalla formalizzazione e dalla successiva sperimentazione di un modello PEI-ICF. Nel contributo sono descritte le fasi di elaborazione del modello e presentati i risultati del percorso di sperimentazione e di monitoraggio messo in atto in alcune istituzioni scolastiche del territorio.